Risk Factors of Pertussis Among Older Adults in South Korea: A Nationwide Health Data-Based Case–Control Study - Hyungwoo Kim; Ju-Young Shin; Jing Chen; Ju Hwan Kim; Yunha Noh; Hee Jin Cheong; Yeon-Mok Oh; Adrienne Guignard; Sumitra Shantakumar (Infectious Diseases and Therapy, 2023)
Abstract Introduction To better understand the conditions associated with pertussis diagnosis among older adults in South Korea, a matched case–control study was conducted of individuals ≥ 50 years diagnosed with pertussis between 2009 and 2018. Methods Pertussis cases were identified using the nationwide Health Insurance Review and Assessment service (HIRA) database. Each case was then matched to up to 10 controls identified using the National Health Insurance Service–National Sample Cohort (NHIS-NSC) by age, sex, and geographic region at index date. In the 12 months and 30 days prior to index date, the presence of clinical characteristics previously reported to be related to pertussis and pertussis-like conditions were assessed, respectively. A conditional multivariate logistic regression model was then used to calculate odds ratios (ORs) of pertussis diagnosis, adjusted for each of the characteristics. Results Pertussis cases (n = 1004) generally demonstrated a higher prevalence of comorbidities compared to controls (n = 9710). Pre-existing asthma and chronic obstructive pulmonary disease (COPD) within 12 months of index date were associated with a two-fold increased risk of pertussis with adjusted ORs (95% confidence interval) of 2.08 (1.68–2.58) and 2.32 (1.59–3.39), respectively. Gastroesophageal reflux disease [GERD; 2.67 (2.23–3.19)], cancer [1.68 (1.23–2.31)], cardiovascular disease [1.62 (1.31–2.00)], renal disease [1.56 (1.12–2.16)], autoimmune disease [1.50 (1.25–1.79)], and hyperlipidemia [1.43 (1.16–1.77)] were also associated with pertussis diagnosis. Finally, acute respiratory events within 30 days prior to index date, such as pneumonia, acute bronchitis, and upper respiratory tract infection (URTI), were highly associated with increased odds of pertussis diagnosis [adjusted ORs of 8.28 (5.10–13.44), 4.86 (3.84–6.14), and 2.90 (2.30–3.67), respectively]. Conclusions This study’s findings complement and expand upon previous studies on the adult pertussis population, generating real-world data to describe underlying clinical characteristics of those diagnosed with pertussis in South Korea.